Role of the complex enzyme immunoassay testing in diagnosing uveitis in the presence of herpetic infection - S.R. Medjidova (Journal of Ophthalmology, 2015)
Background: In recurrent uveitis, establishing whether any herpetic infection has played an etiological or triggering role in the disease is important for selecting the appropriate treatment.